Facial Eco-Friendly Synthesis of Copper Oxide Nanoparticles Using Chia Seeds Extract and Evaluation of Its Electrochemical Activity - Noha Al-Qasmi (MDPI AG, 2021)
In the current study, copper oxide nanoparticles (CuO NPs) were synthesized using chia seed extract in a simple, rapid, and eco-friendly manner for the first time. The synthesized CuO NPs were characterized using different analytical techniques. The images of field emission scanning electron microscopy revealed that the CuO NPs were triangular and pyramid in structure, with a mean particle size of 61.5 nm. The absorption peak of the synthesized CuO NPs was measured using ultraviolet-visible spectroscopy and was recorded at a wavelength of 291 nm. The results of energy-dispersive X-ray analysis confirmed that the CuO NPs synthesized using chia seed extract yielded high-purity CuO NPs. Moreover, the X-ray diffraction analysis indicated the highly crystalline nature of the CuO NPs, and the X-ray photoelectron spectroscopy results indicated that the CuO NPs were prepared successfully. Additionally, electrochemical impedance spectroscopy measurements revealed excellent electrocatalytic conductivity and fast electron transfer at the electrode/electrolyte interface of the synthesized CuO NP-modified glassy carbon electrode.